Effects of position and injury status on associations between preseason workload and heart-rate variability profiles in American college football players - Flatt, A. A.; Allen, J. R.; Keith, C. M.; Esco, M. R. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To quantify position-specific associations between heart-rate-variability profile characteristics and external-workload parameters in American college football players during preseason camp while accounting for injury-related participation status.